Governance and Accountability of Macroeconomic Variables in Indonesia, Malaysia, Thailand and India Using Three Models - Jati, Kumara; Salam, Aziza Rahmaniar (Pusat Pengembangan Kompetensi Aparatur Perdagangan, 2021)
Abstract Fluctuation in macroeconomics variables has given a difficulty to interested parties to implement good governance and appropriate accountability to accelerate sustainable development. This is a research to understand how to maintain stability of macroeconomic variables and its relations with partner countries. This study takes the examples of three major countries in Asia, Indonesia-Malaysia-Thailand (IMT), and India. Moreover, public sector openness and public administration need to facilitate information disclosure and increased cooperation between countries. Based on VAR model, the shock effect of macroeconomic variables (exchange rates, interest rates and foreign exchange reserves) vary each other. The existence of shock indicates the transmission among variables indirectly through intermediate channel, such as: capital, commodity and money market between 4 countries. Model ARMA-ARCH/GARCH and STSM shows macroeconomic variables in IMT and India will be relatively maintained and stable in 2022. Good governance should be based on principles of accountability, innovation, integration, and collaboration. Economic structure similarity and diplomatic relations established for decades have made IMT and India able to help each other to facilitated information disclosure and increased cooperation between the countries. However, the presence of shock from outside remains to be watched out as the global changes can disrupt the sustainable development. Abstrak Fluktuasi variable ekonomi makro telah memberikan kesulitan bagi pihak yang berkepentingan untuk menerapkan Tata Kelola yang baik dan Akuntabilitas yang tepat untuk mempercepat pembangunan berkelanjutan. Ini adalah penelitian untuk memahami bagaimana menjaga stabilitas variable ekonomi makro dan hubungannya dengan negara-negara mitra. Studi ini mengambil contoh tiga negara utama di Asia, Indonesia-Malaysia-Thailand (IMT) dan India. Selain itu, keterbukaan sektor publik dan administrasi public perlu memfasilitasi keterbukaan informasi dan peningkatan kerjasama antar negara. Berdasarkan model Vector AutoRegression (VAR), Shok variable ekonomi makro (nilai tukar, suku bunga dan cadangan devisa) bervariasi satu sama lain. Keberadaan shok menunjukkan adanya transmisi antar variable secara tidak langsung melalui saluran perantara, seperti: pasar modal, pasar komoditas dan pasar uang antara 4 negara. Model ARMA-ARCH/GARCH dan Struktural Time-Series Model (STSM) menunjukkan bahwa variable ekonomi makro di IMT dan India akan relatif dapat dipertahankan dan stabil pada tahun 2022. Tata Kelola yang baik harus didasarkan pada prinsip-prinsip akuntabilitas, inovasi, integrasi, dan kolaborasi. Kemiripan struktur ekonomi dan hubungan diplomatik yang dibangun selama beberapa decade telah membuat IMT dan India dapat saling membantu untuk memfasilitasi pengungkapan informasi dan peningkatan kerjasama antar negara. Namun, keberadaan shok dari luar masih harus diwaspadai karena perubahan global dapat mengganggu pembangunan berkelanjutan.